2009
DOI: 10.1007/s00421-009-1109-3
|View full text |Cite
|
Sign up to set email alerts
|

Time trial performance in normal and high ambient temperature: is there a role for 5-HT?

Abstract: The original central fatigue hypothesis suggested that fatigue during prolonged exercise might be due to higher 5-HT activity. Therefore, we examined the effects of acute administration of a selective 5-HT reuptake inhibitor (SSRI) on performance and thermoregulation. Eleven healthy trained male cyclists completed four experimental trials (two in 18 degrees C, two in 30 degrees C) in a double-blind randomised crossover design. Subjects ingested either a placebo (PLA: lactose 2 x 10 mg) or citalopram (CITAL 2 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
3
39
0
Order By: Relevance
“…Some studies Wilson & Maughan, 1992) diagnosed reduced performance after administration of paroxetine and fluoxetine (reuptake inhibitors of 5-HT). However, most studies (Pannier, Bouckaert, & Lefebvre, 1995;Parise, Bosman, Boecker, Barry, & Tarnopolssky, 2001;Roelands et al, 2009) couldn't confirm these findings. Strüder and Weicker (2001) suggested the reduced performance capacity occurred after acute administration of 5-HT reuptake inhibitors may be as a result of the reduced functional capacity of 5-HT as a multipurpose generator that provides adaptability of neural network to address the needs of the central critical demands, not because of the increased activity of 5-HT.…”
Section: Neurotransmitters and Central Fatiguementioning
confidence: 96%
See 1 more Smart Citation
“…Some studies Wilson & Maughan, 1992) diagnosed reduced performance after administration of paroxetine and fluoxetine (reuptake inhibitors of 5-HT). However, most studies (Pannier, Bouckaert, & Lefebvre, 1995;Parise, Bosman, Boecker, Barry, & Tarnopolssky, 2001;Roelands et al, 2009) couldn't confirm these findings. Strüder and Weicker (2001) suggested the reduced performance capacity occurred after acute administration of 5-HT reuptake inhibitors may be as a result of the reduced functional capacity of 5-HT as a multipurpose generator that provides adaptability of neural network to address the needs of the central critical demands, not because of the increased activity of 5-HT.…”
Section: Neurotransmitters and Central Fatiguementioning
confidence: 96%
“…Furthermore, microinjection of apomorphine (an agonist of DA) into the hypothalamus of rat creates a DA mediated fall of temperature (Brown, Gisolf, & Mora, 1982). Besides, DA release in PO/AH during the treadmill exercise was risen , and DA caused to the increased temperature of the rats body (Myers & Yaksh, 1968), It can be expected that changes in the concentration of these neurotransmitters, helps to the changes in temperature regulation because of fatigue, especially when the exercise is being done in the hot environment (Roelands et al, 2009).…”
Section: Temperature and Central Fatiguementioning
confidence: 99%
“…During exercise, the acute ingestion of the drug in humans has been shown to improve time-trial exercise performance in a warm environment, despite higher body temperatures (Watson et al, 2005). In contrast to acute bupropion administration, the chronic ingestion of the drug does not influence time-trial exercise performance under the same environmental conditions, aside from inducing lower body temperature values than the temperatures observed during the acute bupropion study (Roelands et al, 2009;Watson et al, 2005). The mechanism for these observed discrepancies in bupropion administration seems to be the possible adaptation of central neurotransmitter homeostases during the treatment (Roelands et al, 2009).…”
Section: Brain Monoamines and Other Neurotransmitters On The Developmmentioning
confidence: 96%
“…The data led to the hypothesis that elevated serotonin content may contribute to poor exercise performance during periods of excessive training. A special focus has been given to the pharmacological manipulations used to elucidate the relationship between increased serotonergic activity and the early onset of fatigue (Bailey et al, 1993;Roelands et al, 2009). A study by Bailey et al (1993) demonstrated that exercise performance benefitted from the use of a serotonin antagonist, while treatment with a serotonin agonist led to a detriment in exercise performance.…”
Section: Serotoninmentioning
confidence: 99%
See 1 more Smart Citation